Antiviral activity of lambda-carrageenan prepared from red seaweed (Gigartina skottsbergii) against BoHV-1 and SuHV-1 - Diogo, Jésica Victoria (2015)
The antiviral effect of polysaccharides has been known for many years. Carrageenans are considered a good alternative for the prevention of a wide range of diseases, mainly caused by enveloped viruses. The advantages lie on their high availability, low cost and low induction of resistance. The aim of this study was to evaluate the sensitivity of two viral pathogens of veterinary interest to the presence of lambda-carrageenan. This is the first report of a lambda-carrageenan having antiviral activity against animal viruses belonging to the Alphaherpesvirinae subfamily, BoHV-1 (bovine herpesvirus type 1) strain Cooper and SuHV-1 (suid herpesvirus type 1) strain Bartha. Lambda-carrageenan was able to reduce infectivity of both viruses with a more pronounced effect against BoHV-1. These results proved, as previously shown for human herpes virus type 1, that these compounds could be used as potential antiviral agents in the veterinary field.